To begin solving the equation \( 512x + 23x = 37 \), we can simplify it as follows:
-
Combine like terms on the left side: \[ (512 + 23)x = 37 \] This simplifies to: \[ 535x = 37 \]
-
To find \( x \), divide both sides by 535: \[ x = \frac{37}{535} \]
Now, we can analyze the steps given:
- \( x = 37 \): Incorrect, as we found \( x = \frac{37}{535} \).
- \( x = 6 \): Incorrect, as we found \( x = \frac{37}{535} \).
- \( 37x = 6 \): This step is not directly correct based on the original equation.
- \( 376x = 37 \): This is incorrect; we had \( 535x = 37 \).
- \( 112x + 23x = 37 \): This is not correct based on the original equation.
Based on this analysis, the only correct simplification leading from the original equation is: \[ 535x = 37 \]
None of the proposed steps accurately reflect valid operations or solutions derived from the initial equation.